Friction, fragmentation, and diversity : localized politics of European memories - Salmi-Niklander, Kirsti; Laine, Sofia; Salmesvuori, Päivi; Savolainen, Ulla; Taavetti, Riikka (Heritage and memory studies., 2022)
This collection focuses on difficult memories and diverse identities related to conflicts and localized politics of memories. The contemporary and history-oriented case studies discuss politicized memories and pasts, the frictions of justice and reconciliation, and the diversity and fragmentation of difficult memories. The collection brings together methodological discussions from oral history research, cultural memory studies and the study of contemporary protest movements. The politicization of memories is analyzed in various contexts, ranging from everyday interaction and diverse cultural representations to politics of the archive and politics as legal processes. The politicization of memories takes place on multiple analytical levels: those inherent to the sources; the ways in which the collections are utilized, archived, or presented; and in the re-evaluation of existing research.